Applied energy and mass balance optimization re-engineering: case on Industri Gula Glenmore, Ltd. - Saptyaji Harnowo; Arif Hidayat; Ramit Gupta (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The Glenmore Sugar Industry, Ltd. is designed for 8000 TCD production or 273 TPH. The process required approximately 136 TPH based on the Steam on Cane (SoC) 50%. As the factory's primary input, Sugar Cane cannot supply 8000 TCD Factory Capacity, so 6000 TCD is chosen as an alternative. After commissioning, a lack of steam for servicing the process occurred because the Turbine at full load required 7,6 Kg/kWh. Desuperheater supports the additional steam for the process, which is only 20 TPH. Meanwhile, the steam from the turbine supplies 84 TPH. The need for 32 TPH must be solved, and a specific strategy should be prepared. The Applied Thermodynamics Re-Engineering is a potential method that can be applied in which the findings show that the deficit of 32 TPH steam for the process can be solved precisely.